TECHNOLOGY OF OPTIMAL HARMONY USE OF PEDAGOGICAL TECHNIQUES TECHNIQUES AND INNOVATIVES ARE IMPORTANT EFFECTIVE TRAINING TOOLS FUTURE SPECIALIST (Pedagogy of Higher and Secondary Education, 2022)
In the given article the author shows the way of using pedagogical methods and innovations. The article deals with different aspects of a teacher readiness to educate taking in account the modern priorities of education.